(3JMaI GdCfGe aj aVGFd GdTGes - (3CMeO Hf eMeO, GdHUQhj, TeS GdOjf CHh GdYHGS , GHf ,J (B1015 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HdG HOGjI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B85s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B361 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B489 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B81 s
Keywords: (3GdJGQjNs